Faktor Resiliensi Keluarga yang Merawat Anggota Keluarga dengan Skizofrenia - Iklima Iklima; Syarifah Rauzatul Jannah; Hermansyah Hermansyah; Suryane Sulistiana Susanti; Mudatsir Mudatsir (Journal of Telenursing (JOTING), 2021)
This study aims to determine the resilience factors of families who care for family members with schizophrenia. The research method used a cross-sectional design with a total sample of 114 families of clients with schizophrenia. The data were analyzed using the chi-square test statistic and logistic regression using the stepwise method. The results showed that 51.8% of families had high resilience. The p-value obtained for emotion regulation, impulse control and self-efficacy is 0.0001, while optimism is 0.021. As for the causal analysis, the p-value = 0.851, empathy is 0.574 and achievement is 0.851. In conclusion, self-efficacy is the most dominant predictor associated with the family resilience of schizophrenic clients. Keywords: Family, Resilience, Schizophrenia